2010
DOI: 10.1371/journal.pone.0013779
|View full text |Cite
|
Sign up to set email alerts
|

The Regulation of miRNA-211 Expression and Its Role in Melanoma Cell Invasiveness

Abstract: The immediate molecular mechanisms behind invasive melanoma are poorly understood. Recent studies implicate microRNAs (miRNAs) as important agents in melanoma and other cancers. To investigate the role of miRNAs in melanoma, we subjected human melanoma cell lines to miRNA expression profiling, and report a range of variations in several miRNAs. Specifically, compared with expression levels in melanocytes, levels of miR-211 were consistently reduced in all eight non-pigmented melanoma cell lines we examined; th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

21
235
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 187 publications
(257 citation statements)
references
References 61 publications
21
235
1
Order By: Relevance
“…5B). Furthermore, it has been shown that MITF regulates TRPM1 gene expression as well as the expression of miR-211-5p, as it resides in the sixth intronic region of TRPM1 (21,22). A significant up-regulation of TRPM1 was confirmed by qPCR (Fig.…”
Section: Braf Inhibition Up-regulates Mir-211-5p Expression Through Mmentioning
confidence: 78%
“…5B). Furthermore, it has been shown that MITF regulates TRPM1 gene expression as well as the expression of miR-211-5p, as it resides in the sixth intronic region of TRPM1 (21,22). A significant up-regulation of TRPM1 was confirmed by qPCR (Fig.…”
Section: Braf Inhibition Up-regulates Mir-211-5p Expression Through Mmentioning
confidence: 78%
“…18 miR-211 functions as a metabolic switch 19 and as a potent tumor suppressor in vitro influencing gene pathways involved in cell invasion. [20][21][22] It is located within the noncoding sequence (intron 6) of Melastatin-1 (MLSN-1) gene, 20 which is expressed at high levels in melanocytic nevi but significantly reduced in metastatic melanomas with variable expression in primary lesions. 23 Loss of MLSN-1 mRNA is predictive of significantly reduced disease-free survival of melanoma patients.…”
mentioning
confidence: 99%
“…In comparison with miRNAs that are overexpressed in melanoma, little is known about miRNAs that are diminished during melanoma progression [127], so even less is known about miRNAs downregulated in melanoma metastasis. Fortunately, there is some information in this area and we will present it here.…”
Section: Micrornasmentioning
confidence: 99%